Validation of the MetaMax II Portable Metabolic Measurement System - Larsson, P. U.; Wadell, K. M. E.; Jakobsson, E. J. I. (International Journal of Sports Medicine, 2004)
The purpose of this study was to investigate the validity of the MetaMax II portable metabolic measurement system against the Douglas Bag technique. Nine recreationally active male subjects were included in a validation at 100 W, 10 well-trained male subjects at 200 W and 10 well-trained males at 250 W and at maximal exercise (volitional fatigue at a mean workload of 325 W). All testing was performed on an electronically braked bicycle at 60 rpm. At 100 W, the influence on MetaMax II measurements of adding a Douglas Bag breathing valve in series to the MetaMax II was investigated. The oxygen uptake was, for the MetaMax II, at 100 W mean 0.03 l x min (-1) higher (p < 0.01), at 200 W mean 0.02 l x min (-1) (n. s.) lower, at 250 W mean 0.04 l x min (-1) (n. s.) higher, and at 325 W mean 0.11 l x min (-1) (p < 0.05) higher. The carbon dioxide excretion was, for the MetaMax II, at 100 W mean 0.06 l x min (-1) (p < 0.01) lower, at 200 W mean 0.11 l x min (-1) (p < 0.05) lower, at 250 W mean 0.03 l x min (-1) (n. s.) lower, and at 325 W mean 0.16 l x min (-1) (p < 0.05) lower. The addition of a breathing valve in series to the MetaMax II resulted in lower breathing frequency, a higher ventilated tidal volume, and an affected gas measurement validation. In conclusion, the MetaMax II was found to be valid for metabolic gas measurements between 100 and at least 250 W.